Tribal Women’s Empowerment and Development of Tribal Societies in West Bengal - Maiti, Dilip (Journal of Innovation in Education and Social Research, 2024)
Handicrafts, rudimentary food preparation, and sales are frequently the primary occupations of tribal women in West Bengal. Women are also more likely to engage in homestead farming and micro-enterprises. In this study, we looked at how tribal communities in West Bengal have evolved and how this has affected the status of tribal women. This study's methodology is based on a descriptive survey. Only 1,146 women from different ethnic groups in West Bengal were included in the research. The current study's sample was selected using the stratified random sampling approach. Based on Lickart's five-point scale, the researchers have created their own questionnaire. The researchers in this study employed t-tests, means, and standard deviations for their data analysis. The study's findings shed light on how empowering tribal women contributes to the progress of tribal communities in West Bengal. Because they put in greater hours and are responsible for running the household and the family business, women play a more central role in tribal communities than in other types of society.